ANALISIS SOFTWARE DEVELOPMENT KIT & METODE AUGMENTED REALITY: TINJAUAN SISTEMATIS - Adinto Prasetyo (Universitas Sarjanawiyata Tamansiswa, 2021)
Software Development Kit in Augmented Realityis used to make a software development process more efficient & time-saving, but the SDK itself has many varieties, this makes developers confused in determining which SDK to use.So that as a developer in the AR field, determining the SDK used is a very influential role in the process of running AR applications. Purpose: to provide knowledge of the SDK & the methods used for AR development are very diverse.Methods: this literature review using PRISMA guidelines.Google Scholar are databases used to collect articles with predetermined keywords. 127 articles obtained from the Google Scholar, checking the relevance of articles and evaluating articles with quality assessment. Results: research articles suggest that there are SDK that are widely used & the methods used for AR development in the specified timeframe. Conclusion: Vuforia’s AR SDK is more widely used. There are other SDKs used & there are 2 methods for AR development, namely Marker-Based, & Marker-Less.It is hoped that in the future, SDKs that arenot widely used will be used more often, maybe developers don’t know that there are so many SDKs that can be used and other methods can be used for AR development.